PERAN BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) DALAM PENYELESAIAN SENGKETA KONSUMEN - Wahjuningati, Edi (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2025)
Article 1 point (1) of UUPK states that consumer protection is an effort to ensure legal certainty in order to provide protection to consumers. Therefore, consumers get protection in conducting trade transaction activities. The purpose of this study is to determine and analyze the regulation of consumer protection in Indonesia and the role of BPSK in consumer protection. The formulation of the problems taken in this study (1) How is the regulation of consumer protection in Indonesia and (2) What is the role of BPSK in consumer protection This research is a normative legal research with a statutory approach and concept approach. Legal materials use primary and secondary legal materials. Legal materials are collected through document review and literature study. The results of the research were analyzed using qualitative descriptive techniques. The results of this study are (1) Legal arrangements for consumer protection can be seen in article 5 of Law Number 8 of 1999 concerning Consumer Protection which explains the rights and obligations of consumers and business actors, (2) The role of BPSK is to have enforcement authority in the field of consumer protection law in order to save consumer disputes which if using court channels will take a long time. Keywords: Settlement of consumer disputes, Consumer Dispute Resolution Agency (BPSK)